Development of Hepatic Steatosis After Chemotherapy for Non‐Hodgkin Lymphoma. Issue 2 (28th December 2018) - Ben‐Yakov, Gil; Alao, Hawwa; Haydek, John P.; Fryzek, Nancy; Cho, Min Ho; Hemmati, Mehdi; Samala, Vikram; Shovlin, Margaret; Dunleavy, Kieron; Wilson, Wyndham; Jones, Elizabeth C.; Rotman, Yaron
Abstract : Nonalcoholic fatty liver disease is the most common liver disorder in the developed world. Although typically reflecting caloric overload, it can also be secondary to drug toxicity. We aimed to describe the incidence and risk factors for de novo steatosis during chemotherapy for non‐Hodgkin lymphoma (NHL). In this retrospective case‐control study, adult patients with NHL were treated with rituximab, cyclophosphamide, doxorubicin, prednisone, and vincristine (R‐CHOP) or R‐CHOP + etoposide (EPOCH‐R). Patients with liver disease or steatosis were excluded. Abdominal computed tomography was performed pretreatment and at 3‐ to 6‐month intervals and reviewed for steatosis. Patients with de novo steatosis were matched 1:1 to controls by age, sex, and ethnicity. Of 251 treated patients (median follow‐up 53 months), 25 (10%) developed de novo steatosis, with the vast majority (23 of 25; 92%) developing it after chemotherapy. Of those, 14 (61%) developed steatosis within the first 18 months posttreatment and 20 (87%) within 36 months. Cases had higher baseline body mass index (BMI; mean ± SD, 29.0 ± 6.5 versus 26.0 ± 5.2 kg/m 2 ; P  = 0.014) and hyperlipidemia (12% versus 2%; P  = 0.035). Although their weights did not change during chemotherapy, BMI in cases increased by 2.4 ± 2 kg/m 2 (mean ± SD) from end of treatment to steatosis compared to 0.68 ± 1.4 in controls ( P  = 0.003). Etoposide‐containing regimens were associated with a shorter time to steatosis (median 34 weeks versus 154 weeks; P  < 0.001) despite similar baseline risk factors. Conclusion: The recovery period from NHL chemotherapy appears to be a "hot spot" for development of fatty liver, driven by early posttreatment weight gain, especially in subjects with baseline risk factors. Abstract : Our current study evaluates the development of liver steatosis after chemotherapy treatment for Non Hodgkin Lymphoma. This study suggests that the recovery period from treatment appears to be a "hot spot" for development of fatty liver, driven by early post‐treatment weight gain, especially in subjects with baseline risk factors and should be addressed in post remission follow up monitoring.